Hospitalizations due to primary care‑sensitive conditions among children under five years of age: cross‑sectional study - Araujo, Erika Morganna Neves de; Costa, Gabriela Maria Cavalcanti; Pedraza, Dixis Figueroa (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Hospitalizations due to primary care-sensitive conditions constitute an important indicator for monitoring the quality of primary healthcare. This study aimed to describe hospitalizations due to primary care-sensitive conditions found among children under five years of age (according to their age and sex), in two cities in Paraíba, Brazil. DESIGN AND SETTING: Cross-sectional study carried out in the municipalities of Cabedelo and Bayeux, in Paraíba, Brazil. METHODS: Data were collected from four public pediatric hospitals in Paraíba that receive children from these municipalities. Hospital admission authorizations were consulted to gather information on the children’s profile and the characteristics of their hospitalizations. Differences in the causes of admissions and the respective lengths of hospital stay length were analyzed according to age group and sex. RESULTS: The proportion of hospital admissions due to primary care-sensitive conditions was 82.4%. The most frequent causes were: bacterial pneumonia (59.38%), infectious gastroenteritis and its complications (23.59%) and kidney and urinary tract infection (9.67%). Boys had higher frequency of hospitalizations due to primary care-sensitive conditions than girls. The median hospitalization due to primary care-sensitive conditions was found to be four days. The duration of hospital stays due to primary care-sensitive conditions was significantly longer than those due to conditions that were not sensitive to primary care. CONCLUSIONS: High rates of hospital admissions due to primary care-sensitive conditions were highlighted, especially among children of male sex, with long periods of hospitalization.